Blockchain revolution : how the technology behind Bitcoin and other cryptocurrencies is changing the world / Don Tapscott and Alex Tapscott. - Tapscott, Don, 1947-; Tapscott, Alex (Penguin Business, 2019)
This title explains why the blockchain technology that powers Bitcoin will fundamentally change the internet - what it does and how we use it. The internet is great for collaboration and exchanging information, but deeply flawed when it comes to commerce and transactions. It allows people to commit fraud, collect personal data and invade users' privacy. By contrast, blockchain technology is private and secure, and all the activity it powers is transparent and incorruptible. With its advent, we will not need to trust each other in the traditional sense, because transparency and trust is built into the system itself. Don and Alex Tapscott examine what blockchain technology means beyond currency and explore its positive applications in commerce, business, education, governance and beyond.